La sacralisation du littoral ifrîqiyen à l’époque hafside - Sébastien Garnier (Revue des Mondes Musulmans et de la Méditerranée)
‘Abd Allâh al-Tijânî’s Riḥla contains a strong ideological charge polarized around the political question of order and violence. This article analyzes the literary manipulation of sacred operated by the author who resorts to characters and stereotypes in order to react, on a symbolic field, to the maritime weakness that affects the Hafsid kingdom – a regional power dominated in the Western Mediterranean Basin. It also examines the local rooting of a war-oriented discourse produced by a frontier society.